Analisis Ragam Lisan dalam Makalah Ilmiah Fakultas Seni Pertunjukan Institut Seni Indonesia Yogyakarta - Rokhani, Umilia (Institut Seni Indonesia Yogyakarta, 2010)
The Presence of Spoken Language Analysis in Students' Scientific Paper at the Faculty of Performing Art, Indonesian Institute of the Art Yogyakarta. Scientific writing, as in students' paper, requires standard writing orderliness. However, such requirement is often neglected due to the presence of the spoken style of language in their scientific papers. The assumption of the presence of spoken language appears in the scientific papers written by the students of the Faculty of Performing Art, especially those who belong to the Departments of Karawitan, Pedalangan, Ethnomusicology, and Dance. The above assumption is proven by employing the theory of bilingual division, i.e. bilingualism and bilinguality. Bilingualism is ones habit to use two languages during his interaction with other people. Meanwhile, bilinguality is ones willingness or ability to use two languages. Thus, the presence of the spoken language in students' scientific papers is considered to be a bilingualism process without bilinguality. Based on this theory, a research on misleading/arms of the presence of spoken language in students 'scientific papers and some factors that influence it is needed Keywords: Scientific paper, spoken language, forms and factors of error.